ヤマトサンミャク チョウサ リョコウ ノ トジ ニオケル ジンコウ ジシン タンサ - 石田, 完; イシダ, タモツ; ISHIDA, Tamotsu (国立極地研究所, 1962)
P(論文) Refraction and reflection seismic studies were made on the route between from Station No. 102 and Station No. 227 during the trip across the Yamato Mountains (See Fig. 1). We used the seismic equipment with 24 recording channels and geophones having the natural frequency of 20 cps (type M-3), supplied by the Electro-Technical Labs. It was mounted on a caboose hauled by a snow-car, as shown in Figs. 2 and 3. The 12 geophones were placed at intervals of 20 m, straightly along the traverse route. The shots for the reflection shooting ranged from 1 to 2 kg of TNT placed in 2 shot-holes, drilled 1 or 2 m apart at depths between 4 m and 6 m in the center of the 12 geophones. Velocity variation with depth for P wave was calculated for Station No. 95 using the equation: h = 1/π∫^D_0cosh^<-1>(V_D)/(V_x)dx, where h=depth at which velocity V_D occurs; x=horizontal distance; V_x=velocities from travel time curve in Fig. 6. The travel time curve was plotted from the results of refraction shooting at Station No. 95. Fig. 7 shows variation of the velocity of P wave with depth. Further, from the curve, density variation with depth in neve was deduced by the equation: ρ=2.21×10^<-4>V_P+0.059, whereρis density in g/cm^3 and V_p is velocity of P wave in m/s. The result is shown in Fig. 12. As is known from the figure the rate of increase of density with depth in this area is larger than in the Ross Shelf and Queen Maud Land. The reflection shooting was performed at intervals of 10 km on the route of 270 km in total length. Ice thickness profile obtained from the seismic prospecting is shown in Fig. 10. As seen in this figure, 3 deep valleys were detected beneath the traverse route. These may be the sources of the Shirase Glacier. departmental bulletin paper